The inside advantage [ the strategy that unlocks the hidden growth in your business - Bloom, Robert H.; Conti, Dave (McGraw-Hill, 2008)
Be the Driving Force Behind Your Company's Growth Robert H. Bloom has discovered that every enterprise has at least one strategic asset-one existing strength-that can form the foundation for future growth. He calls this an Inside Advantage. This strength usually lies unrecognized in an activity the business is currently performing or in a concept or an idea that the business already owns. Finding this hidden potential and becoming well known for it will grow the business. This strategy reflects Bloom's 45 years of experience in growing businesses and brands of every size and type, including famous companies such as Southwest Airlines, T-Mobile, T.G.I. Friday's, Zales, Nestle?, and L'Ore?al, as well as not-so-famous B2B firms, not-for-profit organizations, and start-ups. Now, through his Growth Discovery Process, he is making his strategy available to all people who know their craft but don't know how to craft a growth strategy. Bloom's process is a plain-language path of discovery with only four steps. Whether you are a business leader, a manager, or an entrepreneur, this Growth Discovery Process will enable you to gain a profound insight into the core values of your enterprise. It will guide you to a clear understanding of who your customers are and what your special offerings to those customers should be. Finally, the process will stimulate a host of ideas-what Bloom calls Imaginative Acts-for highlighting your Inside Advantage and making it well known to current and prospective customers. Doing what you're good at and doing it better than anyone else will create growth. The Inside Advantage will help you capture that magic moment when customers will select your product or service over those of your competitors